A genetic approach for analyzing the co-operative function of the tRNA mimicry complex, eRF1/eRF3, in translation termination on the ribosome. Issue 12 (9th June 2014) - Wada, Miki; Ito, Koichi
Abstract : During termination of translation in eukaryotes, a GTP-binding protein, eRF3, functions within a complex with the tRNA-mimicking protein, eRF1, to decode stop codons. It remains unclear how the tRNA-mimicking protein co-operates with the GTPase and with the functional sites on the ribosome. In order to elucidate the molecular characteristics of tRNA-mimicking proteins involved in stop codon decoding, we have devised a heterologous genetic system in Saccharomyces cerevisiae . We found that eRF3 from Pneumocystis carinii (Pc-eRF3) did not complement depletion of S. cerevisiae eRF3. The strength of Pc-eRF3 binding to Sc-eRF1 depends on the GTP-binding domain, suggesting that defects of the GTPase switch in the heterologous complex causes the observed lethality. We isolated mutants of Pc-eRF3 and Sc-eRF1 that restore cell growth in the presence of Pc-eRF3 as the sole source of eRF3. Mapping of these mutations onto the latest 3D-complex structure revealed that they were located in the binding-interface region between eRF1 and eRF3, as well as in the ribosomal functional sites. Intriguingly, a novel functional site was revealed adjacent to the decoding site of eRF1, on the tip domain that mimics the tRNA anticodon loop. This novel domain likely participates in codon recognition, coupled with the GTPase function.